PENGARUH KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP KEPUASAN PELANGGAN (STUDI KASUS INDOMARET KECAMATAN MOWEWE KABUPATEN KOLAKA TIMUR) - Azhari, Muh Ashar; Sinarwati, Sinarwati; Madi, Riski Amalia (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo)
The purpose of this research ; (1) To determine the quality of service and customer satisfaction (case study of Indomaret Mowewe District, East Kolaka Regency), (2) to determine the effect of brand image on customer satisfaction (case study of Indomaret, Mowewe District, East Kolaka Regency), (3) to determine the effect of quality service and brand image on customer satisfaction (a case study of Indomaret, Mowewe District, East Kolaka Regency). The population in this study is the general public of Indomaret customers in Mowewe District, East Kolaka Regency. The sample in this study amounted to 100 respondents using the Lemeshow method. The data collection method in this study used multiple linear regression analysis. The results showed that: (1) service quality and brand image had a significant effect on customer satisfaction. (2) service quality has a positive and significant effect on customer satisfaction. (3) service quality and brand image on customer satisfaction have a positive and significant effect.